The Effect of Mesenchymal Stromal Cells Derived From Endometriotic Lesions on Natural Killer Cell Function - Abomaray, Fawaz; Wagner, Arnika Kathleen; Chrobok, Michael; Ekblad-Nordberg, Åsa; Gidlöf, Sebastian; Alici, Evren; Götherström, Cecilia (Frontiers in Cell and Developmental Biology, 2021)
Endometriosis is an inflammatory disease that presents with ectopic endometriotic lesions. Reduced immunosurveillance of these lesions has been proposed to be playing a role in the pathology of endometriosis. Mesenchymal stromal cells (MSC) are found in ectopic lesions and may decrease immunosurveillance. In the present study, we examined if MSC contribute to reduced immunosurveillance through their immunosuppressive effects on natural killer (NK) cells. Stromal cells from endometriotic ovarian cysts (ESCcyst) and eutopic endometrium (ESCendo) of women with endometriosis and their conditioned medium were used in co-cultures with allogeneic peripheral blood NK cells. Following culture, NK cells were examined phenotypically for their expression of activating, inhibitory, maturation, and adhesion receptors and co-receptors, as well as the degranulation (CD107a) marker and the immunostimulatory (interferon-γ) and immunosuppressive (transforming growth factor beta 1 and interleukin-10) cytokines. Moreover, NK cell cytotoxicity was examined using chromium 51 release killing assays. There were no differences between ESCcyst and ESCendo regarding their effects on NK cell cytotoxicity in both conditioned medium and direct co-culture experiments. Additionally, there were no differences between ESCcyst and ESCendo regarding their impact on NK cells’ phenotype and degranulation in both conditioned medium and direct co-culture experiments. Although there were no differences found for DNAX accessory molecule-1 (DNAM-1) and NKp44, we found that the expression of the NK cell ligand CD155 that binds DNAM-1 and proliferating cell nuclear antigen (PCNA) that binds NKp44 was significantly less on ESCcyst than on ESCendo. These findings were not supported by the results that the expression of the known and unknown ligands on ESCcyst for DNAM-1 and NKp44 using chimeric proteins was not significantly different compared to ESCendo. In conclusion, the results suggest that ectopic MSC may not contribute to reduced immunosurveillance in endometriosis through their inhibitory effects on NK cells. This suggests that NK cell inhibition in the pelvic cavity of women with endometriosis develops due to other factors.